Breast Cancer Awareness Survey - Ilyas, Areej; Zulfiqar, Taiba; Ali, Abid (Medical Science Journal for Advance Research, 2022)
Background: Breast cancer is the most frequent malignancy among women. Early detection of breast cancer is critical for reducing the disease’s morbidity and mortality. Therefore, extreme cautions are required. And if it discovered late, it may have bad prognosis. Objective: The goal of this study was to establish whether university students were aware of breast cancer, its symptoms, and the risk factors associated with it, as well as the level of knowledge and awareness of BSE and mammography. METHODS: The current research employed a cross-sectional strategy.A questionnaire was self-administered to all the students. A total of 122 respondents completed the online survey that enrolled in various universities in Punjab. Results: The age of study participants was ranged between 21_30years.Most of them were aware if breast cancer.(73.8%) (90) of students know about brrast cancer through social media, being the most important source of information.Regardi g different aspect of study 78.7% (96) had the knowlegde of risk factor i.e Breast cancer occur mostly with increasing age.An adequate number if participants 77.9% (95) have the knowlegde of self examination. To educate people about breast cancer, we should host seminars. because raising awareness of cancer is essential for early identification and more proactive health-seeking. Despite the fact that breast cancer is relatively widespread in both developing and wealthy nations, broad public awareness is still low. No matter how old or young a woman is, breast care is a need. Conclusion: According to this survey, majority of the participants have basic information about breast cancer and its risk factors. Many participants also know about breast self-examination as it is a simple, quick, non-invasive, and costfree technique for women to check their own breasts for any changes that could be an early indicator of breast cancer in the early stages, when the disease can be treated successfully, boosting the survival rate from breast cancer. any participants also have information about mammography and its advantages in detection of cancer. Hence students are aware of breast cancer.